Assessment of Structured Music Creation Using Compositional Hierarchical Diffusion Model in Music Using Intelligent Fuzzy Information Based Algorithm - Ru Wen (IEEE Access)
This paper offers an evaluation of structured music creation using a new method that combines the information-based algorithm of the Circular Power Maclaurin Symmetric Mean (CPMSM) with the Compositional Hierarchical Diffusion Model (CHDM). The originality of this paper lies in the introduction of the CPMSM algorithm, which includes symmetry and circularity to handle the aggregation of musical elements, ensuring balance and clarity in the final composition a feature unexplored in previous methods. The suggested model creates and refines musical elements at different levels of complexity by making use of the hierarchical structure seen in music composition. To ensure balance and clarity in the final composition, the CPMSM algorithm is introduced to handle the aggregation of musical elements with symmetry and circularity. We create the Weighted CPMSM (WCPMSM) operator, which highlights significant aspects of the composition, to address uncertainty and its significance in musical elements. To verify the reliability of the CPMSM operators, their essential characteristics, idempotency, boundedness, and monotonicity are examined. Moreover, the CHDM is used to create a comprehensive decision-making algorithm for organized music composition. Sensitivity analysis is carried out by adjusting the sensitive factors to assess the efficacy of the suggested approach. This is followed by a comparison study with alternative approaches, which highlights the innovative and applicable nature of this technique in the context of organized music composition.